Adaptive Asset Allocation Strategy Using The Black-Litterman And Carhart Four Factor Approach In The Indonesian Stock Market - Ardian Okta Kristanto; Irwan Adi Ekaputra (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This research explores a new asset allocation framework that integrates the Carhart asset pricing model with the Black-Litterman portfolio optimization model to provide portfolio management decision recommendations. The aim of this research is to test whether this integration can offer optimal portfolio formation strategies for short, medium, and long-term investments in the Indonesian stock market. Analysis was conducted using data from the Indonesia Stock Exchange from 2010 to 2024. This model was then compared with the IHSG, CAPM, and Mean-Variance Model as measured by the Sharpe Ratio to prove that the model can outperform the market and these models. This strategy-based model creates more optimal portfolios and is expected to provide valuable insights for portfolio management literature and broader applications in investment practice. The research results are expected to provide practical contributions to portfolio management in the Indonesian stock market by delivering more adaptive and superior asset allocation strategies.